Cover Picture: Screening of Activation Tools to Design Sulfated Saccharides (ChemistrySelect 30/2017). Issue 30 (23rd October 2017) - Ledru, Hélène; D'Attoma, Joseph; Bostyn, Stéphane; Routier, Sylvain; Buron, Frédéric; Lopin‐Bon, Chrystel
Abstract : The cover picture shows an artist's representation of a competition between three activation modes, thermal, microwaves and flow continuous conditions to achieve regioselective sulfation of various sugar moities. The artist depicts each activation mode as supercar and the aim of the race is to reach the best sulfation conditions. Using microwaves or flow chemistry considerably enhances the rate of the reaction, and these two activation modes are very efficient compared to the slower thermal conditions. We acknowledge Laurent Robin for the design of this drawing. Further details of the winners can be found in the communication paper by Ledru et al . (DOI:10.1002/slct.201701853 )